Chemotherapy induced thrombocytopenia treated by four types of platelets concentrates - Nikolić Ljubinka I.; Nedeljković Ninoslav D.; Jelić Svetislav B.; Suvajdžić Vuković Nada D.; Fillipović-Lješković Ivana M.; Marković Srđan Z.; Janković Drina Lj; Kastratović Dragana A. (Srpsko lekarsko drustvo, 2015)
Introduction: Serious adverse event of anticancer chemotherapy is glanulocytopenia and thrombocytopenia which can decrease efficiency of final therapy results. After many years, platelet concentrates transfusion (PCT) is still researching problem without sure standpoint. The aim: To determine whether there is a difference in the clinical efficiency in the use of 4 types of platelet applied for transfusion; - to ascertain whether platelet count increase expressed as corrected count increment (CCI), is a better parameter for the evaluation of platelet transfusion efficiency than the bleeding time (Bt), as the only readily assessable in vivo platelet function related parameter. Subjects and methods: This paper is a part of academic (noncommercial) IV phase observational nointervetion study. Investigation included 78 patients diagnosed with malignant lymphoma and metastatic solid tumors, transfused by platelet concentrates. Patients were devided into 4 groups, based on the type of platelet concentrates used for transfusion. Results: Patients, were transfused with total number of 647 PC units (235 units were non-leukodepleted and 412 units were leukodepleted). Mean number of PC transfusions per patient was 8.3 PC units, and 4.8 PC unit per one transfusion episode. Before PCT: platelets values were: 18.1 x109/L ±13.1, Bt 8.4±6.1min, and after PCT were 28.2 x109/L ±22.1, 4.7±4.4 min respectively ((p<0.01). Mean CCI value was 13.8±30.4. CCI was corrected in 196/129 PCT and Bt in 122/129 PCT. After supportive therapy using PCs Bt was corrected and became similar in all 4 groups. Discussion: Clinical output is the most important parameter for treatment decision because many patients can tolerate prolonged periods of profound thrombocytopenia without serious bleeding problems. Conclusion: In all 4 investigated groups of patients bleeding time was a far better parameter compared with CCI for the PC therapy efficiency. Authors suggest to be careful and follow clinical and laboratory results personalized to single patient. There is a need to develope better therapies and guidelines so the practice of platelet therapy can be expected to improve in the future.